Perception of health professionals about neonatal palliative care - Ernestina Maria Batoca Silva; Maria José Machado Silva; Daniel Marques Silva
ABSTRACT Objective: To identify the perception of health professionals about neonatal palliative care. Method: A phenomenological qualitative study, a non-probabilistic sample, of 15 health professionals from a neonatal intensive care unit in northern Portugal. Content analysis was performed. Results: Despite their lack of training in palliative care, the health professionals showed concern for the dignity, quality of life and comfort of the newborn and family. They expressed emotional and relational difficulties in following the trajectories of serious illness and death and in the ethical decisions regarding the end-of-life. Conclusion: It is emphasized that professionals are sensitive to pain and suffering and reveal dedicated and committed in the care of the newborn and family. They are available to train and embrace the current challenges posed by the constitution of pediatric palliative care teams and to help achieve an organizational culture that advances in such care.